Economic aspects of semi-continuous construction on multi-storey braced steel frames - Mahmood Md. Tahir, 1962-; A. Aziz Deraman, 1948-; Che Wan Fadhil Che Wan Putra; APSEC '2000 (2000 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2000)
09